2015
DOI: 10.1007/s11240-015-0796-1
|View full text |Cite
|
Sign up to set email alerts
|

Embryogenic potential of immature zygotic embryos of Passiflora: a new advance for in vitro propagation without plant growth regulators

Abstract: In vitro strategies for Passiflora have been developed owing to its economic and ecological importance. However, plantlet regeneration through somatic embryogenesis has presented some problems, such as the reproducibility of the protocol and formation of abnormal embryos and plantlets. Thus, this study aimed to establish a protocol exploring the embryogenic potential of immature zygotic embryos (IZE) of the wild species Passiflora miniata Vanderpl. and Passiflora speciosa Gardn. Friable calli, which formed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
1
7
0
5
Order By: Relevance
“…For P. cincinnata, somatic embryogenesis was induced from zygotic embryos cultured in medium supplemented with a high auxin/cytokinin balance (18.1 µM 2,4-D and 4.5 µM BA). Based on this system, other authors have reported successful induction of somatic embryos for other ornamental Passiflora species, such as P. miniata (Ferreira et al, 2015), P. alata, and P. crenata (Rosa et al, 2015). However, for P. suberosa, only adventitious bud formation was observed when zygotic embryos were cultured in the same conditions established for P. cincinnata (Rosa et al, 2015).…”
Section: Micropropagation Of Wild Passiflora Spp With Ornamental Potmentioning
confidence: 90%
See 1 more Smart Citation
“…For P. cincinnata, somatic embryogenesis was induced from zygotic embryos cultured in medium supplemented with a high auxin/cytokinin balance (18.1 µM 2,4-D and 4.5 µM BA). Based on this system, other authors have reported successful induction of somatic embryos for other ornamental Passiflora species, such as P. miniata (Ferreira et al, 2015), P. alata, and P. crenata (Rosa et al, 2015). However, for P. suberosa, only adventitious bud formation was observed when zygotic embryos were cultured in the same conditions established for P. cincinnata (Rosa et al, 2015).…”
Section: Micropropagation Of Wild Passiflora Spp With Ornamental Potmentioning
confidence: 90%
“…Among the micropropagation systems established for Passiflora, organogenesis is the main morphogenetic pathway of regeneration (Otoni et al, 2013) (Table 1), although recent research has demonstrated the occurrence of regeneration via embryogenesis (Silva et al, 2009(Silva et al, , 2015Paim Pinto et al, 2011;Rosa et al, 2015;Ferreira et al, 2015). With only a few exceptions (Moran Robles, 1978), the MS growth medium (Murashige and Skoog, 1962) has been used.…”
Section: Micropropagation Of Wild Passiflora Spp With Ornamental Potmentioning
confidence: 99%
“…Rocha et al (2012) y Pinto et al (2010) estudiando la embriogénesis en MS suplementado con 2.4-D (4 mgL -1 ) + BA (1 mgL -1 ) y, Rosa y Dornelas (2012), también comprobaron que concentraciones de 2,4-D (3 y 4 mgL -1 ) combinados con BA (1 mgL -1 ) fueron las más efectivas para la regeneración de plantas a partir de callos de P. foetida; así mismo, reportaron la conversión de embriones somáticos bien formados a plantas, alcanzando el 60% de plantas aclimatizadas en invernadero. No obstante, Tavares et al (2015) obtuvieron altos porcentajes (90%) de regenerantes normales a partir de embriones zigóticos inmaduros en medio MS + vitaminas B5 sin 2,4-D, en contraste con los valores de plántulas regeneradas a partir de EZM hasta entonces reportadas por otros autores (60%).…”
Section: Discussionunclassified
“…La familia Passifloraceae comprende aproximadamente 16 géneros distribuidos en regiones tropicales y subtropicales (Pacheco et al 2016) y fue descrita por Lineo (Linnaeu 1753) (Tavares et al 2015). El género Passiflora comprende aproximadamente 575 especies (Aguirre-Morales et al 2016, Jørgensen et al 2012 distribuidas desde el sur de Argentina hasta el sur de Estados Unidos; además, aproximadamente 20 especies se limitan a las regiones tropicales y subtropicales del Sudeste de Asia, Australia y Nueva Zelanda (Hansen et al 2006).…”
Section: Introductionunclassified
“…é uma espécie silvestre nativa da Amazônica Meridional brasileira, podendo também ser também encontrada na Bolívia, Colômbia, Peru, assim como Venezuela e Guianas (LIM, 2012). Tem sido extensivamente cultivada de forma errônea como Passiflora coccinea, devido às características similares das flores de coloração vermelho intenso (VANDERPLANK, 2006 somente foram relatados no estabelecimento de protocolo de embriogênese somática (FERREIRA et al, 2015).…”
Section: Introductionunclassified